Women Empowerment In Select Pantene Tv Commercials (Journal of Namibian Studies : History Politics Culture, 2023)
To open up the eyes of the community about the usefulness of advertisements not just in patronizing products and service but also in spreading advocacies, this study analyses how Pantene TV commercials depict women empowerment specifically looking into the propaganda techniques employed in the commercials, images of women empowerment; and the images of values integration. This study reveals that the propaganda techniques such as glittering generalities and testimony used in the commercials of Pantene are not just a marketing strategy but also a means that runs a cause boosting the confidence of every woman. The images of women empowerment are shown through scenes of the commercials about women fervently pursuing other walks of life aside from merely being a domestic or housewives, and redefining standard of uprightness, sense of responsibility and beauty in the patriarchal society. The selected Pantene TV commercials are observed not to be totally subliminally profit oriented since they also reflect values that promotes women empowerment. The virtues of assertiveness, determination, resiliency, persuasiveness, contentment, steadfastness, flexibility, confidence, valor and character are integrated in the commercials. Thus, the selected Pantene TV Commercials depicts women empowerment by integrated virtues that help women pursue non-domestic walks of life and refine standard of uprightness, responsibility and beauty imposed by culture. Since the propaganda techniques are seen to be a powerful tool both in marketing a product and teaching values, there must be a study on how effective these kinds of commercials are. Considering that the selected Pantene TV commercials show images of women empowerment, there must also be a study on the unconsciousness inferiority complex women have as reflected in beauty products. Taking into consideration the values integration seen to be present in the selected Pantene TV Commercials, there must also be study on the effects of TV commercials to human values.